Association of Self-reflection With Cognition and Brain Health in Cognitively Unimpaired Older Adults. (27th September 2022) - Demnitz-King, Harriet; Gonneaud, Julie; Klimecki, Olga M.; Chocat, Anne; Collette, Fabienne; Dautricourt, Sophie; Jessen, Frank; Krolak-Salmon, Pierre; Lutz, Antoine; Morse, Rachel M.; Molinuevo, José Luis; Poisnel, Géraldine; et al.
Abstract : Background and Objectives: Self-reflection (the active evaluation of ones thoughts, feelings, and behaviors) can confer protection against adverse health outcomes. Its effect on markers sensitive to Alzheimer disease (AD), however, is unknown. The primary objective of this cross-sectional study was to examine the association between self-reflection and AD-sensitive markers. Methods: This study used baseline data from cognitively unimpaired older adults enrolled in the Age-Well clinical trial and older adults with subjective cognitive decline from the SCD-Well clinical trial. In both cohorts, self-reflection was measured via the reflective pondering subscale of the Rumination Response Scale, global cognition assessed via the Preclinical Alzheimer's Cognitive Composite 5, and a modified late-life Lifestyle-for-Brain-Health (LIBRA) index computed to assess health and lifestyle factors. In Age-Well, glucose metabolism and amyloid deposition were quantified in AD-sensitive gray matter regions via fluorodeoxyglucose- and AV45-PET scans, respectively. Associations between self-reflection and AD-sensitive markers (global cognition, glucose metabolism, and amyloid deposition) were assessed via unadjusted and adjusted regressions. Furthermore, we explored whether associations were independent of health and lifestyle factors. To control for multiple comparisons in Age-Well, false discovery rate–corrected p values ( p FDR ) are reported. Results: A total of 134 (mean age 69.3 ± 3.8 years, 61.9% women) Age-Well and 125 (mean age 72.6 ± 6.9 years, 65.6% women) SCD-Well participants were included. Across unadjusted and adjusted analyses, self-reflection was associated with better global cognition in both cohorts (Age-Well: adjusted-β = 0.22, 95% CI 0.05–0.40, p FDR = 0.041; SCD-Well: adjusted-β = 0.18, 95% CI 0.03–0.33, p = 0.023) and with higher glucose metabolism in Age-Well after adjustment for all covariates (adjusted-β = 0.29, 95% CI 0.03–0.55, p FDR = 0.041). Associations remained following additional adjustment for LIBRA but did not survive false discovery rate (FDR) correction. Self-reflection was not associated with amyloid deposition (adjusted-β = 0.13, 95% CI −0.07 to 0.34, p FDR = 0.189). Discussion: Self-reflection was associated with better global cognition in 2 independent cohorts and with higher glucose metabolism after adjustment for covariates. There was weak evidence that relationships were independent from health and lifestyle behaviors. Longitudinal and experimental studies are warranted to elucidate whether self-reflection helps preserve cognition and glucose metabolism or whether reduced capacity to self-reflect is a harbinger of cognitive decline and glucose hypometabolism. Trial Registration Information: Age-Well: NCT02977819; SCD-Well: NCT03005652.